Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1007/s00125-005-1931-z
|View full text |Cite
|
Sign up to set email alerts
|

Beta cell dysfunction in patients with acute myocardial infarction but without previously known type 2 diabetes: a report from the GAMI study

Abstract: Aims/hypothesis: Patients with acute myocardial infarction (AMI) but without previously known type 2 diabetes have a high prevalence of undiagnosed IGT and type 2 diabetes. Such perturbations have dismal prognostic implications. The aim of this study was to characterise AMI patients in terms of insulin resistance and beta cell function. Methods: A total of 168 consecutive AMI patients were classified by means of an OGTT before hospital discharge as having NGT, IGTor type 2 diabetes. The homeostasis model asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0
2

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 43 publications
2
43
0
2
Order By: Relevance
“…A previous evaluation of the present patients revealed that they had beta cell dysfunction [24]. It has been speculated that the combination of low IGF-I and decreased insulin function makes the patient more prone to developing AGT, causing a high postprandial glucose level [25] which has been shown to be a more apparent predictor of subsequent cardiovascular events than fasting glucose [26].…”
Section: Discussionmentioning
confidence: 87%
“…A previous evaluation of the present patients revealed that they had beta cell dysfunction [24]. It has been speculated that the combination of low IGF-I and decreased insulin function makes the patient more prone to developing AGT, causing a high postprandial glucose level [25] which has been shown to be a more apparent predictor of subsequent cardiovascular events than fasting glucose [26].…”
Section: Discussionmentioning
confidence: 87%
“…The prognostic role of hyperglycemia has also been reported in cardiogenic shock complicating acute myocardial infarction [9][10][11][12]. Insulin resistance, known to be part of the glyco-metabolic response to stress, has been investigated in a few studies by means of the Homeostatic Model Assessment (HoMA index), in the early phase of acute myocardial infarction [13] and in ACS patients [14]. In non-diabetic STEMI patients submitted to PCI, we report that insulin resistance, as assessed by HOMA-index, is quite common, and helps in the early risk stratification, since it represents an independent predictor for in-hospital mortality [15].…”
Section: Introductionmentioning
confidence: 99%
“…Insulin resistance is known to be part of the glycometabolic response to stress, but few studies assessed the role of insulin resistance, evaluated by means of Homeostatic Model Assessment (HOOMA index), in the early phase of acute myocardial infarction [12,13]. In non-diabetic STEMI patients undergone PCI, we reported that insulin resistance, as assessed by HOMA index, is quite common and helps in the early risk stratification, since it represents an independent predictor for in-hospital mortality [14].…”
Section: Introductionmentioning
confidence: 99%